Facile synthesis of Fe3O4/hierarchical-Mn3O4/graphene oxide as a synergistic catalyst for activation of peroxymonosulfate for degradation of organic pollutants. Issue 27 (23rd February 2015) - Yang, Bo; Tian, Zhang; Wang, Bin; Sun, Zebin; Zhang, Li; Guo, Yaopeng; Li, Haizhen; Yan, Shiqiang
Abstract : Well-characterized Fe3 O4 /hierarchical Mn3 O4 /rGO composites exhibited high catalytic ability towards the degradation of MB using PMS as an oxidant. Abstract : Highly effective Fe3 O4 /Mn3 O4 /reduced graphene oxide (rGO) hybrids were synthesized as a heterogeneous catalyst for the degradation of organic dyes in aqueous solution using sulfate radical-based advanced oxidation processes. The physicochemical properties of the composite were characterized by several techniques, such as X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectra (FTIR), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and Brunauer–Emmett–Teller (BET) theory. The effects of different parameters on the catalytic activity of Fe3 O4 /Mn3 O4 /rGO, including initial Methylene Blue (MB) concentration, peroxymonosulfate (PMS) concentration, catalyst dosage, pH value, and temperature were assessed. Typically, 98.8% removal of 50 mg L −1 of MB and 68.3% reduction of TOC could be achieved in 30 min under the following conditions: temperature 25 °C, 100 mg L −1 of catalyst, and PMS dosage of 0.3 g L −1, showing a significant enhancement of the catalytic activity of the catalyst in the degradation of organic pollutants in aqueous solution compared with Fe3 O4 /rGO and Mn3 O4 /rGO. The catalyst exhibited high stability and good reusability according to three successive repeated reactions. Based on the radical experiments, the catalytic activity of Fe3 O4 /Mn3 O4 /rGO hybrids for degradation of MB is closely related with the amount of the sulfate and hydroxyl radicals generated from PMS. The excellent catalytic performance of the Fe3 O4 /Mn3 O4 /rGO is mainly attributed to the synergistic effects of Fe3 O4, Mn3 O4, rGO, and Oxone.